OPINI AUDIT SEBAGAI PEMODERASI PENGARUH INTELLECTUAL CAPITAL, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PROPERTI, REAL ESTATE DAN KONTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2014- - Maria Hendriani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
This study aims to determine the effect of intellectual capital, profitability, and leverage on firm value that is moderated by audit opinions on property, real estate and building construction companies listed on the Indonesia Stock Exchange in 2014-2017. Exogenous variables in this study are intellectual capital, profitability and leverage. Endogenous variables in this study are company values, and moderation variables in this study are audit opinions. The data analysis technique used in this study is Partial Least Square (PLS). The results of this study indicate that intellectual capital, profitability and leverage have no effect on company value, and audit opinion has a significant effect on firm value, but audit opinion does not moderate the effect of intellectual capital, profitability and leverage on firm value